Acceptability and Impact of the Empowerment Strategy from the KIPAS Perspective containing the Trisula Values to Elevate the Resilience of Students: Are Both Proven? - Madoni, Ely Roy; Hidayah, Nur; Ramli, M; Indreswari, Henny; Hakam Baihaqi, Muhammad (Universitas Negeri Padang, 2023)
This study aims to delineate the framework and content of an empowerment strategy that integrates Trisula ideals and is based on the KIPAS framework, with the intention of fostering student resilience. In addition, the purpose of this study is to assess, from a KIPAS standpoint, the impact of the empowerment strategy that incorporates Trisula values in fostering greater resilience among students. The stages of this model for research and development were modified from those of Borg and Gall. The student resilience scale is utilized by the instrument that measures student resilience. In the implementation phase, eight junior high school students from the Darul Ulum Islamic Boarding School in Indonesia participated as research subjects. For the purpose of evaluating products, format and model assessment sheets are utilized. Expert evaluation data on format and content were analyzed utilizing Aiken's Value analysis. The findings of the study indicate that the structure and substance of the empowerment approach, which incorporates Trisula values as viewed through the lens of KIPAS, are suitable for assisting students in developing resilience. Additionally, it was deemed a success that this research product assisted students in developing resilience. Further recommendations for future researchers are to broaden the range of subjects included in effectiveness testing, thereby enabling the application of model products beyond Islamic boarding schools.